RISK ASSESSMENT OF BENZENE, TOLUENE, ETHYLBENZENE, AND XYLENES (BTEX) IN PAINT PLANTS OF TWO AUTOMOTIVE INDUSTRIES IN IRAN BY USING THE COSHH GUIDELINE - Farshad, Aliasghar; Oliaei, Hamid Khabazi; Mirkazemi, Roksana; Bakand, Shahnaz (European Scientific Journal, ESJ, 2014)
Objectives: The purpose of this study was to assess the risk Benzene, Toluene, Ethylbenzene, and Xylenes in the paint plants of two automotive industries in Iran by using the COSHH guideline and by measuring the ambient concentration of these chemicals. Method: This cross sectional study was conducted in two phases, in phase one the BTEX ambient concentration was measured in three unites of paint plants according to the method advised by OSHA12. In the second phase, the COSHH data collection forms were used for a qualitative risk assessment and were distributed among 90 randomly selected workers (45 in each industry). Results: In both industries, maximum risk rating was for benzene followed by toluene, which showed moderate to high risk level for these two chemicals in both industries. Mean ambient concentration of benzene and toluene were 34.9 and 4.4 times of Iranian standard Threshold Limit Value in industry no 1, and 9.5 and 1.9 times of Iranian standard Threshold Limit Value in industry no 2, respectively. The level of concentration of BTEX and the risk rating in industry number 1 was significantly more than that of industry number 2. Conclusion: This study revealed the need for control of Benzene and Toluene in work place, and also showed that the COSHH risk assessment showed a similar result to the actual measuring of the same substances.